Decreasing returns to scale for the small country due to scarcity or indivisibility a test on sport - Glejser, Herbert (Center for Economic Studies <München>: CESifo working paper series, 2000)
This paper envisages economies of scale - or rather, diseconomies of low scale - caused in small nations by a sometimes acute shortage of talent and to indivisibility of teams: for example, a small country such as Iceland or Luxembourg cannot participate in an international football tournament with only three players, even if they are exceptionally gifted. After devising a few models the author tests them on sports (especially on Olympic results). He finds that, indeed, the comparative superiority of large nations is to be found in (especially large) team events. Several results are significant at the 0.001 significance level. He concludes by suggesting the establishment of institutions similar to customs unions: a European Sport Associations United (ESAU) could fight with some hope the giants of today and tomorrow (China, India, etc).